PENGUATAN DAYA SAING UMKM MELALUI DIVERSIFIKASI PRODUK KERUPUK BERBASIS LABU KUNING - Fatkhurahman Fatkhurahman; Arizal N; Aznuriyandi Aznuriyandi (Jurnal Pengabdian Kompetitif, 2025)
Micro, Small, and Medium Enterprises (MSMEs) face the challenge of increasingly fierce competition, particularly related to limited product variety and low added value from local raw materials. This community service activity aims to strengthen the competitiveness of MSMEs through product diversification using pumpkin crackers as a local food innovation. The target group was members of the Graha Permai Joint Business Group (KUB), which consists of household-scale business owners. The activity was conducted on January 18, 2026, using outreach, demonstrations, and hands-on practice in making pumpkin crackers. The material provided included an introduction to the potential of pumpkin, the importance of product innovation, the stages of the production process, and business development opportunities. The results of the activity demonstrated an increase in participants' knowledge and skills in processing pumpkin into marketable crackers. Furthermore, this activity fostered entrepreneurial awareness and the KUB members' interest in innovating other products using available local raw materials. This community service activity contributed to increasing MSME production capacity, expanding product variety, and creating opportunities for sustainable income generation. Thus, pumpkin-based product diversification can be an effective strategy for strengthening the competitiveness of MSMEs based on local potential.